The abilities of improved schizophrenia patients to work and live independently in the community: a 10-year long-term outcome study from Mumbai, India - Srivastava, Amresh Kumar (BioMed Central, 2009)
BACKGROUND: The outcome of first episode schizophrenia has several determinants. Socioecological factors, particularly living conditions, migration, community and culture, not only affect the level of risk but also the outcome. Mega cities around the world show a unique socioecological condition that has several challenges for mental health. The present study reports on the long-term status of patients with schizophrenia in such a mega city: Mumbai, India. AIM: This study aims to reveal the long-term outcome of patients suffering from schizophrenia with special reference to clinical symptoms and social functioning. METHODS: The cohort for this study was drawn from a 10-year follow-up of first episode schizophrenia. Patients having completed 10 years of consistent treatment after first hospitalisation were assessed on psychopathological and recovery criteria. Clinical as well as social parameters of recovery were evaluated. Descriptive statistics with 95% confidence intervals are provided. RESULTS: Of 200 patients recruited at the beginning of this study, 122 patients (61%) were present in the city of Mumbai at the end of 10-year follow-up study period. Among 122 available patients, 101 patients (50.5%) were included in the assessment at the end of 10-year follow-up study period, 6 patients (3.0%) were excluded from the study due to changed diagnosis, and 15 patients (7.5%) were excluded due to admission into long-term care facilities. This indicates that 107 out of 122 available patients (87.7%) were living in the community with their families. Out of 101 (50.5%) patients assessed at the end of 10 years, 61 patients (30.5%) showed improved recovery on the Clinical Global Impression Scale, 40 patients (20%) revealed no improvement in the recovery, 43 patients (72.9%) were able to live independently, and 24 patients (40%) were able to find employment. CONCLUSION: With 10 years of treatment, the recovery rate among schizophrenia patients in Mumbai was 30.5%. Among the patients, 87.7% of patients lived in the community, 72.9% of patients lived independently, and 40% of patients obtained employment. However, 60% of patients were unable to return to work, which highlights the need for continued monitoring and support to prevent the deterioration of health in these patients. It is likely that socioecological factors have played a role in this outcome.